1983
DOI: 10.1515/zna-1983-0804
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SF6 on the Broadening and Shift of the 535.0 nm Thallium Line

Abstract: The pressure broadening and shift of the 535.0 nm Tl line resulting from the photodissociation of thallium iodide mixed with sulfur hexafluoride were studied at low densities using a Fabry-Perot interferometer. A linear variation of both the width and shift of the line with the SF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…thallium lamp operated at 100 Mc/s. The methods of line profile analysis were the same as those in our previous works [1][2][3][4][5]. We have found that the resultant profile of the 535.0 nm T1 line of thallium iodide molecules can be fitted sufficiently well to a Voigt profile which is the convolution of the Lorentzian and Gaussian distribution.…”
Section: B) Trioxido-p-quaterphenylmentioning
confidence: 88%
See 4 more Smart Citations
“…thallium lamp operated at 100 Mc/s. The methods of line profile analysis were the same as those in our previous works [1][2][3][4][5]. We have found that the resultant profile of the 535.0 nm T1 line of thallium iodide molecules can be fitted sufficiently well to a Voigt profile which is the convolution of the Lorentzian and Gaussian distribution.…”
Section: B) Trioxido-p-quaterphenylmentioning
confidence: 88%
“…1 the shift A of the 535.0 nm T1 line, which is towards the red, is a linear function of the nitrogen density: A=AQ-\-6N, where d is the pressure shift coefficient and AQ is the residual shift for the Til cell with no perturbing gas. The least-squares analysis yielded the value <5 = (-3.00±0.098) X 10-20 cm _1 /molecule cm- 3 .…”
Section: B) Trioxido-p-quaterphenylmentioning
confidence: 96%
See 3 more Smart Citations